EFFECT OF SEED STORAGE GEOMETRY ON GERMINATION AND GROWTH PERFORMANCE OF WATERMELON (CITRULLUS LANATUS) - Adnan Nuhu, Dahiru; Subair, Rukayat; Oladipupo, Risikat; Rufai, Rukayat (FUDMA Journal of Sciences, 2026)
Watermelon contributes significantly to household nutrition and income generation, particularly in developing countries where it serves as a source of vitamins, minerals, antioxidant and hydration during dry season. However, limited information exists on the influence of seed storage geometry and seed physiological behaviour of crop growth. This study examined the effect of seed storage geometry on the growth performance of watermelon (citrullus lanatus) under controlled greenhouse condition. The experiment was conducted at the Federal University of Agriculture, Abeokuta (FUNAAB), Ogun State, Nigeria. This study assess the effectiveness of eight seed storage treatment which include; pyramid, small icosahedron, big icosahedron, vertical hexahedron, horizontal hexahedron, poly icosahedron, ambient (control) and refrigerator (control). The seed were stored for two, four and six months. The treatment were arranged in a Complete Randomized Design (CRD) with three replications. The key agronomic parameters which include; germination count, germination percentage, leaf area, vine length, number of leaves, fresh weight and dry matter production were measured at 2 and 4 WAP. There was significant differences (P
Keywords: Geometry; Seed, Storage; Growth; Watermelon